BIOLOGY OF CULTIVATION OF STEVIA REBAUDIANA BERTONI PLANT IN UZBEKISTAN - Begmatov Abdusamat Mamatkulovich; Haydarov Mirzokhid Bakhtiyarovich (Galaxy International Interdisciplinary Research Journal, 2022)
Currently, at the stage of rapid development of our society, it is urgent to solve the issues of effective use of plant raw materials in the fields of food, pharmaceuticals, and medicine in order to increase the well-being of the population.